Cannabis-induced bullous lung disease leading to pneumothorax: Case report and literature review. Issue 19 (May 2017) - Mishra, Rashmi; Patel, Ravi; Khaja, Misbahuddin
Abstract: Rationale: Marijuana use has been increasing in the United States among college students and young adults. Marijuana use has been associated with bullous lung disease which can lead to pneumothorax. There are other recreational drugs like methylphenidate, cocaine and heroin which have been associated with pneumothorax. Patient concerns: We present a case of a 30-year-old man with spontaneous pneumothorax associated with marijuana use. The patient had no medical conditions and presented to the emergency room with chest pain. The physical examination revealed decreased breath sound on the right side of the chest. Diagnoses: Bed side ultrasound of chest showed stratosphere sign, absent lung sliding; consistent with right-sided pneumothorax. Interventions and outcomes: The patient underwent placement of a chest tube. Computed tomography chest scans performed on day two also showed bullous lung disease in the right lung. Serial x-rays of the chest showed re-expansion of the lung. Lessons: Despite the beneficial effects of Marijuana there are deleterious effects which are emphasized here. This case highlights the need for further studies to establish the relationship between marijuana use and lung diseases in the absence of nicotine use.